2021
DOI: 10.37333/001c.31305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of International Service-Learning on Students’ Global Citizenship and Intercultural Effectiveness Development

Abstract: International service-learning (ISL) is conceptualized as an intersection of three educational components: service-learning, study abroad, and international education. Its potential benefits include increases in students’ intercultural competence and sense of global citizenship. Arguably, through immersion in a cross-cultural context, students can learn to appreciate diverse values and cultures while enhancing their social responsibility and bringing benefit to a community in need. However, most existing empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…28,29 The study findings also demonstrated that the international service-learning programs are potentially beneficial to the development of intercultural competence by virtue of their immersive nature which facilitates the intercultural interaction; this is the fact that could not be replicated in classrooms and the formal curricular programs. 13 Service learning is also beneficial to students because many employers seek for generic competencies in employees including communication skills, attitude, team working, decision-making, and problem-solving skills, 27 and this was the item admitted by Hong Kong and American students during the group interviews.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…28,29 The study findings also demonstrated that the international service-learning programs are potentially beneficial to the development of intercultural competence by virtue of their immersive nature which facilitates the intercultural interaction; this is the fact that could not be replicated in classrooms and the formal curricular programs. 13 Service learning is also beneficial to students because many employers seek for generic competencies in employees including communication skills, attitude, team working, decision-making, and problem-solving skills, 27 and this was the item admitted by Hong Kong and American students during the group interviews.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] As compared with the conventional service-learning programs, international service learning sets the target of the activity beyond national/regional boundaries and aimed on more international aspects including the intercultural awareness and sensitivity, intercultural competencies, and global citizenship development. 13 It has been applied to disciplines of business, social sciences, law, engineering, etc., 7,8,[14][15][16] while there are limited resources regarding the prosthetics and orthotics (P&O). [17][18][19] Prosthetics and orthotics is an important part of the health care sector for people with disabilities or functional impairments; therefore, it is necessary to enhance P&O students' internationalization education.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations